2021
DOI: 10.51253/pafmj.v71i5.5706
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Nucleated Red Blood Cell (Nrbc) Count Using a Fully Automated Haematology Analyzer Versus Manual Counting

Abstract: Objective: To evaluate the performance of Nucleated RBC (NRBC) Count using a fully automated haematology analyzer versus manual counting. Study Design: Cross-Sectional Study. Place and Duration of Study: Department of Hematology, Armed Forces Institute of Pathology, from Sep 2019-Jun 2020. Methodology: Routine fresh whole blood samples were run on Sysmex XN-3000 automated haematology analyzer and 384 samples with results of ≥0.1% Nucleated red blood cells were included in this study. Manual N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
1
2
1
Order By: Relevance
“…They are preferable to manual count by being cost effective and convenient. Previous studies in other countries have been conducted to determine the precision and diagnostic accuracy of Sysmex XN series and they have been very encouraging [2,12]. Our study also shows that Sysmex XN-1000 analyzer with its WNR channel is highly sensitive (90.56%) and specific (88.30%) in enumerating nRBCs.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…They are preferable to manual count by being cost effective and convenient. Previous studies in other countries have been conducted to determine the precision and diagnostic accuracy of Sysmex XN series and they have been very encouraging [2,12]. Our study also shows that Sysmex XN-1000 analyzer with its WNR channel is highly sensitive (90.56%) and specific (88.30%) in enumerating nRBCs.…”
Section: Discussionsupporting
confidence: 67%
“…A previous study conducted in Pakistan showed that Sysmex analyzer measured nRBCs accurately up till 200 counts. Above that its measurement was not accurate [12]. This did not happen in our study.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations